Trade-offs between short-term mortality attributable to NO2 and O3 changes during the COVID-19 lockdown across major Spanish cities - Achebak, Hicham; Petetin, Hervé; Quijal-Zamorano, Marcos; Bowdalo, Dene; Pérez García-Pando, Carlos; Ballester, Joan (Environmental pollution (1987), 2021)
The emergence of the COVID-19 pandemic forced most countries to put in place lockdown measures to slow down the transmission of the virus. These lockdowns have led to temporal improvements in air quality. Here, we evaluate the changes in NO2 and O3 levels along with the associated impact upon premature mortality during the COVID-19 lockdown and deconfinement periods along the first epidemic wave across the provincial capital cities of Spain. We first quantify the change in pollutants solely due to the lockdown as the difference between business-as-usual (BAU) pollution levels, estimated with a machine learning-based meteorological normalization technique, and observed concentrations. Second, instead of using exposure-response functions between the pollutants and mortality reported in the literature, we fit conditional quasi-Poisson regression models to estimate city-specific associations between daily pollutant levels and non-accidental mortality during the period 2010–2018. Significant relative risk values are observed at lag 1 for NO2 (1.0047 [95% CI: 1.0014 to 1.0081]) and at lag 0 for O3 (1.0039 [1.0013 to 1.0065]). On average NO2 changed by −51% (intercity range −65.7 to −30.9%) and −36.4% (−53.7 to −11.6%), and O3 by −1.1% (−20.2 to 23.8%) and 0.6% (−12.4 to 23.0%), during the lockdown (57 days) and deconfinement (42 days) periods, respectively. We obtain a reduction in attributable mortality associated with NO2 changes of −119 (95% CI: -273 to −24) deaths over the lockdown, and of −53 (−114 to −10) deaths over the deconfinement. This was partially compensated by an increase in the attributable number of deaths, 14 (−72 to 99) during the lockdown, and 8 (−27 to 50) during the deconfinement, associated with the rise in O3 levels in the most populous cities during the analysed period, despite the overall small average reductions. Our study shows that the potential trade-offs between multiple air pollutants should be taken into account when evaluating the health impacts of environmental exposures. [Display omitted] •COVID-19 lockdown and deconfinement periods led to strong reductions in NO2 levels.•The decrease in NO2 concentrations reduced the associated attributablemortality.•The increase in O3 levels partially offset the avoided mortality from reduced NO2.